Novel watermarking based on DIBR 3D image - Chen CUI; Shen WANG; Qiong LI (网络与信息安全学报)
Depth-image-based rendering (DIBR) has become an important technology in 3D displaying with its great advantages.As a result,more and more 3D products copyright problems turn out.Since either the center view with depth image or the synthesized virtual views could be illegally distributed,not only the center views but also the synthesized virtual views need to be protected.A watermarking method for DIBR 3D images was proposed.After applying three-level DWT to the center image,odd-even quantization was utilized to modify the coefficients of the sub-blocks of the center image,by this way the proposed method was made robust to typical signal distortions,such as JPEG compression,noise addition and median filter.As the experimental results shown,the proposed method is much more robust to the common signal distortion attacks with lower BER (bit error rate) compared with existing methods.